غزوات النبی ﷺ میں دور حاضر کے لیے عسکری رہنمائی: Military Guidance for Modern Times In Ghazwat Un-Nabi ﷺ - Hassan Javed, Dr. Faizan; Mariam, Ms.; Barkat, Ms. Tayba (Al-Amīr Research Journal for Islamic Studies, 2024)
This study explores the military strategies and leadership principles demonstrated by Prophet Muhammad ﷺ during his battles (Ghazwat) and examines their relevance for contemporary military and strategic planning. The research analyzes key aspects of the Prophet's ﷺ military conduct, including tactics, resource management, ethical considerations in warfare, and the role of leadership. It aims to extract lessons that can be applied in modern warfare, conflict resolution, and military ethics, highlighting the significance of justice, coordination, psychological warfare, and adaptability in dynamic combat environments. The study seeks to bridge historical military wisdom with modern-day challenges, offering valuable insights for military leaders, policymakers, and researchers in understanding the enduring impact of these historical events on contemporary military thought. Keywords: Seerah, Ghazwat Un-Nabi, Prophet Muhammadﷺ, Islamic History.